2014
DOI: 10.5551/jat.22400
|View full text |Cite
|
Sign up to set email alerts
|

Association between ADAM17 Promoter Polymorphisms and Ischemic Stroke in a Chinese Population

Abstract: Aim: Stroke is a leading cause of death and disability worldwide. Most ischemic strokes (IS) are caused by atherosclerosis. Recently, the pivotal role of ADAM17 in atherosclerosis has been thoroughly addressed. However, the association between ADAM17 and IS has not yet been thoroughly explored. The present study therefore aimed to investigate the association between disintegrin and metalloproteinase 17 (ADAM17) gene polymorphisms and the risk of ischemic stroke (IS). Methods: The associations between five ADAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…A recent study has revealed that the rs11684747 polymorphism has a potential allele-specific binding site for the hepatocyte nuclear factor-1 alpha (HNF1A/B) transcription factor, which is associated with the insulin sensitivity and progression of diabetes [26,39]. Our previous studies have shown that the ADAM17 rs1524668 A>C increases the susceptibility to PACI-type stroke and that the rs12692386 GA/GG genotypes of ADAM17 are linked to high ADAM17 mRNA expression and increase susceptibility to human abdominal aortic aneurysm [28,31]. We speculate that transcriptional enhancers and other regulatory elements in the promoter regions may play various regulatory roles in the gene transcription.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study has revealed that the rs11684747 polymorphism has a potential allele-specific binding site for the hepatocyte nuclear factor-1 alpha (HNF1A/B) transcription factor, which is associated with the insulin sensitivity and progression of diabetes [26,39]. Our previous studies have shown that the ADAM17 rs1524668 A>C increases the susceptibility to PACI-type stroke and that the rs12692386 GA/GG genotypes of ADAM17 are linked to high ADAM17 mRNA expression and increase susceptibility to human abdominal aortic aneurysm [28,31]. We speculate that transcriptional enhancers and other regulatory elements in the promoter regions may play various regulatory roles in the gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Five SNPs (rs55790676, rs12692386, rs11684747, rs1524668 and rs11689958) within the promoter region of ADAM17 were selected according to our previous reports [28,31]. The five ADAM17 genetic variants were genotyped by using the SNaPshot Multiplex Kit (Genesky Biotechnologies, Inc., Shanghai, China).…”
Section: The Isolation Of Dna and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…The OR for ARB use in the study by Yan et al was only adjusted for age, sex and BMI and therefore, could have been affected by residual confounding. On the other hand, it has been shown in a, Chinese population that rs12692386 G promotor polymorphism was associated with higher ADMA17 expression 32 .Moreover, several ACE2 polymorphisms have been reported in different populations including the Chinese. These polymorphisms have been shown to be associated with HTN, DM and CVD as well as with ACE2 activity, and serum ACE2 and angiotensin-(1-7) peptide levels 33 .It remains to be determined whether increased circulating ACE2 levels are due to increased shedding or due to both increased shedding and expression.…”
Section: Discussionmentioning
confidence: 98%
“…The human ADAM17 gene is located on chromosome 2 and contains 19 exons. Accumulating evidence demonstrates that single-nucleotide polymorphisms (SNPs) in the ADAM17 gene are associated with risk for various in ammation-related diseases, such as ischemic stroke, Kawasaki disease and cardiovascular death [17][18][19]. Our previous study revealed, for the rst time that ADAM17 -172A>G may act as a functional SNP involved in sepsis progression [13].…”
Section: Introductionmentioning
confidence: 89%